Penerapan Prinsip Subrogasi Dalam Perjanjian Asuransi Pengangkutan Atas Kerugian Yang Disebabkan Oleh Pihak Ketiga - Raden Rara Sayyidati Alfi Ilmiah Putri; Retno Wulansari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The presence of insurance offers protection and protection to a business / business to handle a risk. Insurance has several principles to regulate the rights and obligations of both parties, one of which is the principle of subrogation. This principle regulates the provisions of third-party liability for the loss of the insured for the negligence of the third party. The research method is a type of normative law research with an approach method through a statutory approach (statue approach) and a conceptual approach that identifies existing principles or doctrinal views to generate new ideas related to the principle of subrogation in transportation insurance. The data collection technique used in this research is through the library research method consisting of books, scientific journals, papers, and relevant internet sources regarding the topics & themes in the research. The technical analysis in this research is descriptive-qualitative. Based on the results of the research conducted, it shows that the implementation of the principle of subrogation against third parties who cause losses to the insured presents several consequences and obstacles that will have an impact on the legal protection of insurance companies. Therefore, it is necessary to reformulate regulations regarding the principle of subrogation in insurance that can provide legal certainty for citizens.